Health risk assessment of staff at Poás Volcano National Park, Costa Rica, due to exposure to SO2 and H2S gasses - Morales-Alpízar, José David (2024)
[Objective] Verify the levels of exposure to SO2 and H2S of park rangers at the Poás Volcano National Park, using OSHA international standards as a reference. [Methodology] SO2 and H2S concentrations were studied from September 2018 to December 2019 and February 2019 to December 2019, respectively using MultiRae portable detection equipment. Sampling points were placed at the ranger’s house, the entrance station, the visitors' center, and the overlook. The level of chemical risk was determined taking into consideration: the workers’ health, exposure time, safety equipment, training, and TWA and STEL values obtained. [Results] The highest SO2 concentration was 16.0 ppm, which was recorded at the visitor center, while the highest H2S concentration was 45 ppm, which was obtained from the park ranger’s house. The average gas concentration was close to the detection limit for both gasses, suggesting that gasses, in general, are not directed toward visitors’ areas. No measurement station exceeded 2 ppm for SO2 in 8 hours (TWA). However, in the visitors’ center and the overlook, SO2 exceeded 5 ppm in 15 minutes (STEL) with concentrations equal to 10.1 ppm and 7.4 ppm, respectively. [Conclusions] Low levels of chemical hazard were obtained for both gasses at the sampling points, except for the visitors’ center which had a medium level.